The Effect of Brand Pleasure, Brand Arousal, and Brand Dominance towards Brand Loyalty in the case of UNIQLO Indonesia - Febe Surya Effendi; Windy Freshia Luhana (iBuss Management, 2023)
Given the growth that has changed significantly, especially during the Covid-19 pandemic, the fashion industry has changed and come back more substantial now. Thus, the fashion industry has become more attractive to explore. This can be seen in one of the global fashion brands, UNIQLO, which aims to dominate the fashion market industry. Therefore, the researchers decided to analyze UNIQLO in Indonesia as the research object. This study will investigate the effect of brand pleasure, brand arousal, and brand dominance on brand loyalty in the case of UNIQLO Indonesia. In addition, this study utilizes a quantitative approach with the simple random sampling method and 75 respondents were engaged. Online questionnaires were used to gather the research data and then were analyzed using multiple linear regression that will be processed using the IBM SPSS approach. Results revealed that brand pleasure, brand arousal, and brand dominance have an effect on brand loyalty. However, brand pleasure has the most significant impact on brand loyalty in the case of UNIQLO Indonesia. Analyzing the relationship between brand pleasure, brand arousal, and brand dominance on brand loyalty towards the fashion industry, specifically UNIQLO Indonesia, will provide many benefits for various parties, including academicians, business professionals, and companies. Keywords: brand pleasure, brand arousal, brand dominance, brand loyalty.